Renal safety of coformulated tenofovir/emtricitabine vs other nucleoside analogues in combination therapy in antiretroviral-naive patients aged 50 years or older in Spain: The TRIP study. Issue 1 (February 2015) - Pedrol, Enric; Caro-Murillo, Ana M.; Castaño, Manuel A.; Riera, Melchor; Olalla, Julián; Domingo, Pere; Arazo, Piedad; Gómez-Sirvent, Juan L.; Pulido, Federico; Romero-Palacios, Alberto; Aguirrebengoa, Koldo; Vera, Francisco; et al.
Abstract : Objectives: Our aim is to describe the impact of emtricitabine (FTC)/tenofovir (TDF) versus other nucleoside reverse transcriptase inhibitor (NRTIs)-based regimens on renal function of human immunodeficiency virus (HIV) naïve patients >50 years old who started combination antiretroviral therapy (cART). Design: National, retrospective cohort analysis of patients >50 years old when they started cART (January 1, 2006–December 31, 2009). Methods: We compared renal safety (changes in estimated glomerular filtration rate [eGFR] during the first year, and time to renal events during 4 years of follow-up) in FTC/TDF versus non-FTC/TDF users. Among FTC/TDF users, we compared protease inhibitors vs non-nucleoside reverse transcriptase inhibitors and Lopinavir/ritonavir vs Efavirenz. Results: We included 103 patients: median age: 54.9 years, 84% males, median CD4 count 247 cells/μl, median viral load 4.7 log; median follow up 18 months (max: 48 months); 73 started with FTC/TDF and 30 with other NRTIs. Change in eGFR was significantly worse for ritonavir-boosted lopinavir (LPV/r) vs efavirenz (EFV) users in the FTC/TDF group (71.2 vs 98.9 ml/min/1.73 m 2 at month 12, P  < 0.05). The risk of renal events (progression to an Chronic Kidney Disease Epidemiology Collaboration value < 60 ml/min/1.73 m 2 in subjects with baseline values >60) was comparable for FTC/TDF users and non users, but was higher and almost significant for LPV/r as compared to EFV users in the FTC/TDF group (adjusted hazard ratio 6.1, 95% CI 0.8–45.5). Conclusions: In our study with a population of HIV infected subjects ≥ 50 years old, renal safety was similar for FTC/TDF and other NRTI-based regimens, but worse for LPV/r as compared to other regimens.